Analisa Lalu Lintas Simpang Tak Bersinyal terhadap Kinerja Bundaran Tugu Juang Kota Jambi - Dicaprio, Muhammad Edward; Yamali, Fakhrul Rozi; Dony, Wari (Universitas Batanghari, 2025)
The Jambi City Tugu Juang roundabout is where Colonel Abunjani Street, Cokroaminoto Street and Captain A. Bakaruddin Street meet. The traffic conditions at this roundabout are quite congested, causing traffic jams, especially during peak hours. The data used in this research are primary and secondary data. In carrying out the analysis, the calculations carried out by researchers were based on the 1997 Indonesian Road Capacity Manual Method (MKJI). The aim of this research was to analyze the roundabout network which includes capacity, degree of saturation, delays and queuing opportunities. As well as analyzing the current level of roundabout service against existing traffic conditions. From the results of the analysis, it is known that the capacity (C) in the BA braid section = 4763.30 pcu/hour, CB braid = 3962.23 pcu/hour, and AC braid = 3228.44 pcu/hour, the degree of saturation (DS) ratio is 0, 80. roundabout delay (DR) is 11.15 sec/pcu, the upper limit of queuing opportunity (QP) is 41.40% and the lower limit is 18.21%, the level of service based on the highest degree of saturation is on the CB interwoven section (HOS. Cokroaminoto street – Captain A. Bakaruddin street) has a service level of D.